2007
DOI: 10.1093/jhered/esm097
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Multiple Paternity in Littorina saxatilis: Hedging the Bets?

Abstract: The mating system of a species can have great effects on its genetic structure and evolution. We studied the extent of multiple paternity in a gastropod with internal fertilization, the intertidal snail Littorina saxatilis. Paternal genotype reconstruction based on microsatellite markers was performed on the offspring of wild, naturally fertilized females from 2 populations. The numbers of males contributing to the offspring per female were among the highest detected in invertebrates so far, with the exception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 55 publications
9
41
2
Order By: Relevance
“…For this, simulation analyses implemented in the software PrDM [43] were run for scenarios of equal, moderately skewed, and highly skewed paternal contribution taking into account a varying number (two to ten) of participant males in a brood. This range of participant males is in accordance with the level of multiple paternity observed in other aquatic gastropods [44,45]. …”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…For this, simulation analyses implemented in the software PrDM [43] were run for scenarios of equal, moderately skewed, and highly skewed paternal contribution taking into account a varying number (two to ten) of participant males in a brood. This range of participant males is in accordance with the level of multiple paternity observed in other aquatic gastropods [44,45]. …”
Section: Methodssupporting
confidence: 88%
“…marine species: [61,45,3,4,5]; freshwater species: [23]). Several decades ago, studies using enzyme electrophoresis reported multiple paternity in freshwater pulmonates such as Biomphalaria obstructa [62], Bulinus africanus [63], B .…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier attempt to estimate the level of multiple paternity in L. saxatilis we detected an average of 7.6 males contributing to broods of wild-mated females [24]. However, we analysed only 20–23 out of 23 to 87 offspring per brood.…”
Section: Introductionmentioning
confidence: 99%
“…), multiply-fertilized individuals accounted for about 76%–100% among all of the studied females, and the number of sires per brood ranged from 1–23. Patterns of sperm competition are variable in these species, some have no male sperm precedence [18], [22], [23] whilst others have last male sperm precedence [16], [19].…”
Section: Introductionmentioning
confidence: 99%